Experiências religiosas, espirituais e anômalas na psicoterapia: relatos dados por psicólogos - Hamazaki, Edson Sigueyoshi (2024)
Despite the large number of scientific studies on the impact of religiosity and spirituality on mental health and the prevalence of religious, spiritual, dissociative, spiritual or mediumistic and anomalous experiences (REDEMA) in the general population, the many myths, fears and prejudices surrounding this topic when linked to the clinical practice of psychologists make it difficult for professionals to deal with these experiences in the psychotherapeutic process. The objective of this study was to assess whether these experiences are reported and/or experienced by patients in the therapeutic setting during psychotherapy and, based on this assessment, to identify and characterize both the experiences and the clinical management performed. Despite the frequent religious and/or spiritual demands presented by patients in the clinical context and the existence of conceptual and clinical tools for managing these conflicts in an ethical and professional manner, this topic has not been addressed in professional training. These experiences can cause considerable apprehension and suffering to patients, requiring specific skills involving knowledge, methods and techniques that psychologists must possess. A survey was conducted using an online questionnaire sent to clinical psychologists involving a nonprobabilistic convenience sample using the snowball method. The data collected included sociodemographic information about the professionals and, mainly, reports of these experiences in clinical practice in addition to the management performed. Quantitative data were analyzed statistically and qualitative data by content analysis. A total of 206 psychologists participated, of which 161 (78.2%) made 299 reports, involving experiences brought by patients to psychotherapy (n = 198), experiences experienced by patients in the therapeutic setting during psychotherapy (n = 40), experiences experienced by psychologists in the therapeutic setting during the psychotherapeutic process (n = 39), reports that did not involve REDEMA experiences (n = 22), in addition to 263 clinical managements performed. All reports and managements were categorized and analyzed, providing a rich overview of these experiences in the psychotherapeutic context. Considering that Psychology is a science and profession in constant movement and evolution, and that, as demonstrated by this study, REDEMA experiences are commonly reported by patients during psychotherapy, and that there is knowledge, skills, competencies and conduct based on scientific evidence, necessary for adequate clinical management of these experiences in professional practice, the existing deficiency in training must be urgently corrected, providing future psychologists with this knowledge and competencies during their undergraduate studies, in addition to providing professionals who are working with training opportunities so that difficulties in approaching these topics can be minimized and patients can be adequately and effectively served according to their needs